2023
DOI: 10.1007/s10342-023-01534-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of Picea abies in response to the artificial inoculation of Heterobasidion parviporum

Abstract: Norway spruce Picea abies is one of Europe’s most economically important tree species. However, it is highly susceptible to the root rot fungus Heterobasidion parviporum. Climate change will benefit the pathogen as the tree host is weakened by, e.g., extended drought. Breeding can improve forest health, and several root rot genetic markers are suggested to improve the resistance of Norway spruce. This study aimed to compare the resistance (here defined as necrosis length) of Norway spruce families and genotype… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Breeding can improve forest health, and several genetic markers for root rot are proposed to improve resistance in these species [22,[105][106][107][108]. In the study [105], the resistance (defined here as necrosis length) of spruce families and genotypes to two strains of H. parviporum was compared under different water availability. The results showed that family and genotype within the family influenced necrosis length, which was related to the aggressiveness of the fungal strains.…”
Section: Selection Of Trees Resistant To H Annosummentioning
confidence: 99%
“…Breeding can improve forest health, and several genetic markers for root rot are proposed to improve resistance in these species [22,[105][106][107][108]. In the study [105], the resistance (defined here as necrosis length) of spruce families and genotypes to two strains of H. parviporum was compared under different water availability. The results showed that family and genotype within the family influenced necrosis length, which was related to the aggressiveness of the fungal strains.…”
Section: Selection Of Trees Resistant To H Annosummentioning
confidence: 99%